Unified regional modeling of GaN HEMTs with the 2DEG and DD formalism - Zhang, Junbin (2013)
This paper presents the unified regional modeling (URM) approach to developing a compact model (CM) for GaN-based high electron mobility transistors (HEMTs) based on the two-dimensional electron gas (2DEG) and drift-diffusion (DD) formalism. It is shown that through the URM of the 2DEG based on triangular well approximation and surface-potential based DD transport, a CM for generic metal-insulator-semiconductor (MIS) HEMTs can be developed, which is scalable over device physical and structural parameters.